Impact of sodium-glucose cotransporter-2 inhibitors on heart failure and mortality in patients with cancer. Issue 6 (9th November 2022) - Chiang, Cho-Han; Chiang, Cho-Hung; Chiang, Cho-Hsien; Ma, Kevin Sheng-Kai; Peng, Chun-Yu; Hsia, Yuan Ping; Horng, Chuan-Sheng; Chen, Cheng-Ying; Chang, Yu-Cheng; See, Xin Ya; Chen, Yuan-Jen; Wang, Shih-Syuan; et al.
Abstract : Objectives: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) reduce heart failure (HF) in at-risk patients and may possess antitumour effects. We examined the effect of SGLT2i on HF and mortality among patients with cancer and diabetes. Methods: This was a retrospective propensity score-matched cohort study involving adult patients with type 2 diabetes mellitus diagnosed with cancer between January 2010 and December 2021. The primary outcomes were hospitalisation for incident HF and all-cause mortality. The secondary outcomes were serious adverse events associated with SGLT2i. Results: From a total of 8640 patients, 878 SGLT2i recipients were matched to non-recipients. During a median follow-up of 18.8 months, SGLT2i recipients had a threefold lower rate of hospitalisation for incident HF compared with non-SGLT2i recipients (2.92 vs 8.95 per 1000 patient-years, p=0.018). In Cox regression and competing regression models, SGLT2i were associated with a 72% reduction in the risk of hospitalisation for HF (HR 0.28 (95% CI: 0.11 to 0.77), p=0.013; subdistribution HR 0.32 (95% CI: 0.12 to 0.84), p=0.021). The use of SGLT2i was also associated with a higher overall survival (85.3% vs 63.0% at 2 years, p<0.001). The risk of serious adverse events such as hypoglycaemia and sepsis was similar between the two groups. Conclusions: The use of SGLT2i was associated with a lower rate of incident HF and prolonged overall survival in patients with cancer with diabetes mellitus.